Impact of pathologic lymph node‐positive renal cell carcinoma on survival in patients without metastasis: Evidence in support of expanding the definition of stage IV kidney cancer. Issue 13 (24th April 2020) - Srivastava, Arnav; Rivera‐Núñez, Zorimar; Kim, Sinae; Sterling, Joshua; Farber, Nicholas J.; Radadia, Kushan D.; Patel, Hiren V.; Modi, Parth K.; Goyal, Sharad; Parikh, Rahul; Mayer, Tina M.; Saraiya, Biren; et al.
Abstract : Background: Stage III renal cell carcinoma (RCC) encompasses both lymph node‐positive (pT1‐3N1M0) and lymph node–negative (pT3N0M0) disease. However, prior institutional studies have indicated that among patients with stage III disease, those with lymph node disease have worse oncologic outcomes and experience survival that is similar to that of patients with American Joint Committee on Cancer (AJCC) stage IV disease. The objective of the current study was to validate these findings using a large, nationally representative sample of patients with kidney cancer. Methods: Patients with AJCC stage III or stage IV RCC were identified using the National Cancer Data Base (NCDB). Patients were categorized as having lymph node‐positive stage III (pT1‐3N1M0), lymph node–negative stage III (pT3N0M0), or stage IV metastatic (pT1‐3 N0M1) disease. Cox proportional hazards models compared outcomes while adjusting for comorbidities. Kaplan‐Meier estimates illustrated relative survival when comparing staging groups. Results: A total of 8988 patients met the inclusion criteria, with 6587 patients classified as having lymph node–negative stage III disease, 2218 as having lymph node‐positive stage III disease, and 183 as having stage IV disease. Superior survival was noted among patients with lymph node–negative stage III disease, but similar survival was noted between patients with lymph node‐positive stage III and stage IV RCC, with 5‐year survival rates of 61.9% (95% confidence interval [95% CI], 60.3%‐63.4%), 22.7% (95% CI, 20.6%‐24.9%), and 15.6% (95% CI, 11.1%‐23.8%), respectively. Conclusions: Current RCC staging systems group pT1‐3N1M0 and pT3N0M0 disease as stage III disease. However, the results of the current validation study suggest the need for further stratification and even placement of patients with pT1‐3N1M0 disease into the stage IV category. Staging that accurately reflects oncologic prognosis may help clinicians better counsel and select patients who might derive the most benefit from lymphadenectomy, adjuvant systemic therapy, more rigorous imaging surveillance, and clinical trial participation. Abstract : The findings of the current study indicate that patients with lymph node‐positive, American Joint Committee on Cancer stage III kidney cancer have survival outcomes that are more similar to those of patients with stage IV disease than their counterparts with stage III disease with no lymph node involvement. Thus, the current study not only validates prior smaller institutional studies but also provides further evidence that patients with lymph node involvement should be considered as having stage IV kidney cancer.